The Effect of Fermentation Time on pH and Total Soluble Solids of Kelud Simplex Pineapple Peel Kombucha - Nadia Shafira Eka Putri; Elysabet Herawati; Dwi Ari Budiretnani (Journal of Biotechnology and Natural Science, 2026)
Kombucha is a functional fermented beverage produced through the symbiotic interaction of bacteria and yeast, and pineapple peel can serve as an alternative substrate due to its fermentable sugar content. This study aimed to determine the effect of fermentation time on pH and reducing sugar content in kombucha made from Kelud Simplex pineapple peel. The experiment used a completely randomized design with eight treatments and three replications over 14 days of fermentation, with observations taken every two days. Data were analyzed using the Shapiro-Wilk normality test, Levene’s homogeneity test, one-way ANOVA, and Tukey HSD post hoc analysis. The pH decreased progressively from 3.68 on day 0 to 2.76 on day 14, while reducing sugar content declined from approximately 11.0% to 8.0%. Statistical result showed that fermentation time significantly affected both pH and reducing sugar content (p > 0.05). These findings indicate that longer fermentation promotes greater acidification and sugar utilization, with the 14 days of fermentation producing the lowest reducing sugar and the highest acidity, indicating more advance stage microbial activity.